Burns in Nepal: A population based national assessment. Issue 5 (August 2015) - Gupta, S.; Mahmood, U.; Gurung, S.; Shrestha, S.; Kushner, A.L.; Nwomeh, B.C.; Charles, A.G.
Highlights Disproportionately burns are greater in low and middle-income countries (LMICs). A lack of data exist for burn epidemiology at a community level in low-income countries outside of Africa. Thus the objective of tis study is to assess burn prevalence at a population level and to provide detailed epidemiology via a population-based countrywide survey in Nepal. In total, 1, 350 households were surveyed with 2, 695 individuals with a response rate of 97%. Fifty-five burn injuries were present in 54 individuals (2.0%, 95% CI 1.5% to 2.6%). The largest proportion of burns was in the age group 25–54, with those aged 0–14 having the second largest proportion. Burn injuries in Nepal appear to be primarily a disease of adults due to scalds, rather than the previously held belief that burn injuries occur mainly in children (0–14) and women and are due to open flames. The data suggest that the demographics and etiology of burn injuries at a population level vary significantly from hospital level data. To tackle the burden of burn injuries, interventions from all the public health domains including education, prevention, healthcare capacity and access to care, need to be addressed, particularly at the community level. Such increased efforts in all spheres would likely lead to significant reduction of burn-related deaths and disability.